Analysis of Spending at Muhammadiyah Australia College - Afriyanto, Juwandi; Andika, Aryan; Munadi, Muhammad (Journal of Comprehensive Science, 2025)
This study aims to analyze the structure and dynamics of Muhammadiyah Australia College (MAC) spending as a community-based Islamic educational institution in Australia in the period from 2021 to 2023.  Using a qualitative descriptive approach and analysis of annual financial data, this study shows a significant shift in the MAC spending structure.  In the early stages of establishment in 2021, spending was dominated by external consulting services.  However, as operations develop, spending in 2022 and 2023 is more focused on internal expenses such as employee salaries, superannuation, educational infrastructure, and information technology.  Although revenues have increased significantly, faster growing expenditures have led to budget deficits that need managerial attention.  The results of this study underscore the importance of efficient, transparent, and strategic financial management in community educational institutions, as well as the need to diversify revenue sources and implement adaptive financial information systems.  These findings are expected to be a reference for similar institutions in improving the efficiency of spending and the sustainability of education operations in the diaspora.